Frontispiece: Potential Therapeutic Applications of MnSODs and SOD‐Mimetics. Issue 20 (10th April 2018) - Bonetta, Rosalin
Abstract : The therapeutic applications of MnSOD encompass different types of therapy, including MnSOD gene therapy and recombinant forms of MnSOD, which can enter specific cells and can be used in conjunction with chemotherapy in order to treat diseases such as cancer. Besides, SOD mimetics, such as cyclic polyamines, salens, porphyrins, nitroxides and PLED mimetics are continuously being synthesised to perform the function of larger enzyme systems, whilst at a cheaper price and having a longer half‐life in the blood. SOD mimetics are being investigated to treat other oxidative stress injuries, which include ischaemia reperfusion injury, inflammation, diabetes and radiation injuries. For more information see the Minireview by R. Bonetta onpage 5032 ff.